Diseño del sistema de costos por órdenes de producción para la Perrada de Pepe Ltda. Nisa Bulevar (2013)
This report presents the results of the internship performed at fast food restaurant La Perrada d 'Pepe LTDA at their main branch located in Bulevar Nisa, whose general objective presents the design of a Costs system that allows a profitable operation.